Effect of BAP (6-Benzyl Amino Purine) Concentration on Growth Micro Cutting of Nepenthes ampullaria - Iman Budisantoso; Mona Indriani; Kamsinah Kamsinah (Biosaintifika: Journal of Biology & Biology Education, 2018)
Conventionally, cultivations of Nepenthes are conducted by using seeds, cutting, and filial separation. However, there are many obstacles come both from time and technical aspect. In vitro culture is an alternative way for cultivating  N. ampullaria (Jack,). One of a technique of in vitro culture is micro cutting. BAP (6-benzyl amino purine) growth regulator could be added to optimize the growth of  N. ampullaria microcutting. The purpose of this research was to determine the effect of  BAP on the growth of Nepenthes microcutting. This research was done experimentally using Completely Randomized Design (CRD). BAP treatment consisted of 5 concentrations: 0; 0.5; 1; 1.5; 2 (ppm), each treatment were multiplied 4 times. The parameters observed were: a time of bud initiation, time of root initiation, total of leaves, total of new buds, total of roots, length of leave, length of root, and height of bud. The data obtained were analyzed with ANOVA (Analisis of Variance) and continued with 5% and 1% LSD (Least Significant Different)  test. The result showed that addition of BAP affected the growth of  N. ampullaria microcutting in total leaves, length of leave, and total of buds. LSD test proved that 0.57 ppm of BAP was optimal concentration to increase total buds, whit the value reached of 3.86. Here, we found that BAP can be utilized to enhanche N. ampullaria growth on in vitro culture. The benefit of this study is to conserve N. ampullaria in vitro using BAP at  0.57 ppm.